Perceived professional development needs of general and adapted physical education teachers - Rosenfeld, Scott S. (My University, 2011)
Students with disabilities should receive adapted physical education (APE) services from a qualified APE and! or a general physical education (GPE) teacher. Current research, however, has shown that many teachers of students with disabilities feel unprepared and lack the confidence to teach these students. To ensme that students with disabilities receive appropriate and quality physical education, APE and GPE teachers should receive relevant professional development. The pmpose of this study was to determine the perceived professional development needs of APE and GPE teachers regarding working with students who have disabilities. A total of 13 8 teachers (APE = 42, GPE = 45, and dual roles in APE/GPE =51) completed an online survey to rank and rate 12 professional development content areas. Results indicated that all of the teachers combined felt they need professional development most in the areas of knowledge of disabilities and teaching and instructional strategies. APE teachers felt that behavior management and teaching and instructional strategies were the most important professional development content areas, while GPE teachers felt that knowledge of disabilities, inclusion techniques, and teaching and instructional strategies were the most important professional development content areas.
Keywords: Education -- Aims and objectives -- United States.; Physical education and training.; Teachers -- Training of -- United States.